Condensed Aerosol Generators in Fire Safety of Buildings. Part 1 – Analysis of Normative and Legal Documents - Robart Śliwiński (Safety & Fire Technology)
Aim: The aim of this paper is to present the construction and principle of operation of condensed aerosol generators, as well as a review of their selected characteristics, confirmed in the process of assessment and verification of constancy of performance. The paper describes selected laboratory tests, including those specific to Group A, B and C fires. Introduction: Fixed firefighting systems, in addition to detection systems (fire alarm system) and alarm systems (voice evacuation systems), are one of the pillars of the safety of today's erected, increasingly complex buildings. However, unlike these detection and alarm systems, fire extinguishing systems based on condensed aerosol generators focus on providing an adequate level of protection for property, as they are dedicated to spaces that are not normally occupied. For this reason, emphasis is placed on the reliability of the generators, whose only task is to trigger appropriately at a specific time and fill the protected area with aerosol. Methodology: The theoretical research, such as analysis of literature and legal documents, synthesis, generalisation, inference, comparison and analogy, was used in the development of the paper. A review of selected characteristics validated in the process of assessment and verification of constancy of performance of the analysed products was carried out. Research processes relating to selected parameters of the generators and inherent in the conformity assessment of construction products are presented. Conclusions: It should be noted that, irrespective of their main purpose, condensed aerosol generators, which are a key component of aerosol fire extinguishing kits, can be crucial not only with regard to the safety of the buildings themselves, but also of their users, influencing the containment of a fire in the extinguishing zone where they are installed. Also, important is the awareness of owners and managers of building structures equipped with condensed aerosol generators. Their particular attention should be directed to the specifics of the generator itself and their knowledge of its operating principles. In the next stages of the work, it will be crucial to define the basics related to the connection of the generators to the installation forming a fixed firefighting system, to identify and describe issues related to design, installation and maintenance, and to identify the risks related to the potential exposure of the users of built structures to the extinguishing aerosol. Keywords: firefighting, condensed aerosol generators, aerosol extinguishing kits, extinguishing agents